Reflexiones sobre el federalismo mexicano : palabras de Diego Valadés al recibir el Doctorado Honoris Causa de la Universidad de Buenos Aires - Valadés, Diego (2015)
"Written version of the oral presentation given on August 27, 2015, during the awarding of the honorary doctorate from the University of Buenos Aires to Diego Valadés. The ceremony took place in the Red Room of the Faculty of Law."